Effectiveness of rotary or manual techniques for removing a 6-year-old filling material - Duarte, Marco Antônio Hungaro; Só, Marcus Vinícius Reis; Cimadon, Vanessa Buffon; Zucatto, Cristiane; Vier-Pelisser, Fabiana Vieira; Kuga, Milton Carlos [UNESP] (FapUNIFESP (SciELO), 2010)
The aim of this study was to evaluate the effectiveness of manual and rotary instrumentation techniques for removing root fillings after different storage times. Twenty-four canals from palatal roots of human maxillary molars were instrumented and filled with gutta-percha and zinc-oxide eugenol-based sealer (Endofill), and were stored in saline for 6 years. Non-aged control specimens were treated in the same manner and stored for 1 week. All canals were retreated using hand files or ProTaper Universal NiTi rotary system. Radiographs were taken to determine the amount of remaining material in the canals. The roots were vertically split, the halves were examined with a clinical microscope and the obtained images were digitized. The images were evaluated with AutoCAD software and the percentage of residual material was calculated. Data were analyzed with two-way ANOVA and Tukey's test at 5% significance level. There was no statistically significant differences (p>0.05) between the manual and rotary techniques for filling material removal regardless the ageing effect on endodontic sealers. When only the age of the filling material was analyzed microscopically, non-aged fillings that remained on the middle third of the canals presented a higher percentage of material remaining (p<0.05) compared to the aged sealers and to the other thirds of the roots. The apical third showed a higher percentage of residual filling material in both radiographic and microscopic analysis when compared to the other root thirds. In conclusion, all canals presented residual filling material after endodontic retreatment procedures. Microscopic analysis was more effective than radiographs for detection of residual filling material.
Keywords: Endodontics; Gutta-percha; Retreatment; root canal filling material; analysis of variance; comparative study; dental debonding; dental equipment; device removal; endodontics; equipment design; histology; human; instrumentation; maxilla; methodology; molar tooth; nonparametric test; radiography; retreatment; time; tooth pulp; Analysis of Variance; Dental Debonding; Dental Equipment; Dental Pulp Cavity; Device Removal; Equipment Design; Humans; Maxilla; Molar; Root Canal Filling Materials; Root Canal Preparation; Statistics, Nonparametric; Time Factors